2023
DOI: 10.3389/fphar.2023.1123415
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferases in renal development, injury, repair, and fibrosis

Abstract: Protein arginine methyltransferases (PRMTs) methylate a range of histone and non-histone substrates and participate in multiple biological processes by regulating gene transcription and post-translational modifications. To date, most studies on PRMTs have focused on their roles in tumors and in the physiological and pathological conditions of other organs. Emerging evidence indicates that PRMTs are expressed in the kidney and contribute to renal development, injury, repair, and fibrosis. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…Research has shown that arginine metabolism promotes skeletal muscle and cardiac fibrosis in patients with muscular dystrophy ( 11 ).Additionally, arginine methylation plays a role in regulating epithelial-mesenchymal transition ( 12 ). Protein arginine methyltransferase has been shown to promote the progression of fibrosis in conditions such as diabetic nephropathy, idiopathic pulmonary fibrosis, and liver cirrhosis ( 13 ). However, the associations between arginine pathway metabolites and fundal FVP in patients with PDR have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that arginine metabolism promotes skeletal muscle and cardiac fibrosis in patients with muscular dystrophy ( 11 ).Additionally, arginine methylation plays a role in regulating epithelial-mesenchymal transition ( 12 ). Protein arginine methyltransferase has been shown to promote the progression of fibrosis in conditions such as diabetic nephropathy, idiopathic pulmonary fibrosis, and liver cirrhosis ( 13 ). However, the associations between arginine pathway metabolites and fundal FVP in patients with PDR have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that arginine metabolism promotes skeletal muscle and cardiac fibrosis in patients with muscular dystrophy (11).Additionally, arginine methylation plays a role in regulating epithelial-mesenchymal transition (12). Protein arginine methyltransferase has been shown to promote the progression of fibrosis in conditions such as diabetic nephropathy, idiopathic pulmonary fibrosis, and liver cirrhosis (13). However, the associations between arginine pathway metabolites and fundal FVP in patients with PDR have not been established.…”
Section: Introductionmentioning
confidence: 99%